Blood Lactate Decreased by Foam Rolling Post-Quarter Marathon - Rahayu, Setya; Ali, Mohammad Arif; Nugroho, Didit Prakosa Adi; Anggita, Gustiana Mega; Kurniawati, Dewi M.; Noer, Etika Ratna; Fibriana, Fidia; Salazar, Sofia Fernández; Mohamed, Ani Mazlina Dewi (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: New training methods, increased volume, the prolonged duration could induce the delayed onset of muscle soreness (DOMS), and it is associated with blood lactate (BL). Foam roller (FR) is known as a tool for active recovery. AIM: The study’s purposes are to assess the effect of the Quarter Marathon (QM) and Foam Roller (FR) on blood lactate (BL). METHODS: This is a pilot study with a quasi-repeated-measures design. Ten trained young males were voluntarily signed up using the purposive sampling technique. The Accutrend-Plus by Roche was used to measure BL. Blood lactate was measured 6 times. Combination FR protocols from the Master of Muscle and Casall were used. Repeated-measures ANOVA test was used to analyze the changes in BL. RESULTS: Blood lactate significantly increased 4.90 ± 3.0 (mmol/L) post-QM as p < 0.05, pre-test 2.23 ± 0.8 (mmol/L) compared to post-running 7.1 ± 2.6 (mmol/L). It was decreased after foam rolling activity 4.33 ± 0.7 (mmol/L), and 3.06 ± 0.5 (mmol/L) at 120 min post-running, then returned to normal after 24 h post-QM 2.44 ± 0.5 (mmol/L). CONCLUSION: Foam rolling potentially decreased BL after QM.